Kinerja Karyawan: Pendekatan Kepemimpinan Transformasional Dan Kerjasama Tim Dimediasi Kepuasan Kerja - Muhammad Taufik Lesmana; Au Raja Rahman Batubara; Alfianita Alfianita; Maulidina Putri Simatupang; M. I. Nasution (JURNAL ILMIAH MANAJEMEN & BISNIS, 2023)
Purpose – This research aims to determine how transformational leadership, teamwork, job satisfaction, and employee performance are related. Additionally, the relationship between transformational leadership, teamwork, and employee performance is examined in this study about the role of job satisfaction as an intervening variable.Method – This study uses a quantitative approach involving employee respondents from Mixue Ice Cream Medan employees, with a sample of 50 respondents. Questionnaires related to research variables were used to collect data by measuring the Likert scale. Statistical analysis to test the hypothesis using SEM PLS (Structural Equation Modeling-Part Least Square).Results – This study found that job satisfaction affects employee performance, and transformational leadership and teamwork affect job satisfaction and employee performance. Furthermore, this research collaboration cannot explain job satisfaction as an intervening variable because there is no indirect effect between transformational leadership and teamwork support; job satisfaction is not an intervening factor.Originality (Novelty) – This study combines three main factors, namely transformational leadership, teamwork, and job satisfaction, and explores the complex relationships among the variables. This research seeks a more comprehensive understanding of the factors influencing employee performance.Implication – Companies must develop transformational leadership strategies, strengthen teamwork, and increase employee job satisfaction to achieve optimal performance. Additionally, this research makes a theoretical contribution to expanding the understanding of the relationship between these variables and the mediating role of job satisfaction in the corporate context.